2009
DOI: 10.1248/cpb.57.464
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hot-Melt Coating Process for Designing a Lipid Based Controlled Release Drug Delivery System for Highly Aqueous Soluble Drugs

Abstract: Hot-melt coating process (HMCP) was applied to develop a lipid based oral controlled release matrix system (tablet) to deliver highly aqueous soluble drugs using paracetamol as a model drug. Granules prepared from paracetamol and particular filler were coated with different levels of lipid and then compressed into tablets to get controlled/sustained delivery of the drug over an optimum period. Process parameters were optimized with particular focus on fluidization pattern during HMCP proposing a 'design space'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In particular, solid lipid particles, at micro‐ and/or nano‐scale, possessing matrix made from fatty acids, glycerides, fatty alcohols and solid waxes with high melting point, behave as drug carriers for a controlled as well as sustained drug release, the lipid coating being impermeable to aqueous media and not immediately permeable to the dispersed drug or ready to be dissolved or solubilized. As a consequence, they can be used for protection of the active drug and/or taste masking 4–8…”
Section: Introductionmentioning
confidence: 99%
“…In particular, solid lipid particles, at micro‐ and/or nano‐scale, possessing matrix made from fatty acids, glycerides, fatty alcohols and solid waxes with high melting point, behave as drug carriers for a controlled as well as sustained drug release, the lipid coating being impermeable to aqueous media and not immediately permeable to the dispersed drug or ready to be dissolved or solubilized. As a consequence, they can be used for protection of the active drug and/or taste masking 4–8…”
Section: Introductionmentioning
confidence: 99%
“…Particles modified by the hot-melt coating process could be not only directly prepared into pellets, but also compacted into tablets or filled into capsules to achieve sustained drug delivery in an optimum period. In a study, the sustained-release tablets were prepared by granules that were made of drug and particular fillers and then coated with different levels of lipid (26). The results showed that the composition of the granule that could be manipulated by changing the amount of lipid in the formulation directly affected the drug release pattern.…”
Section: Conventional Hot-melt Coating Techniquementioning
confidence: 99%
“…The results showed that the composition of the granule that could be manipulated by changing the amount of lipid in the formulation directly affected the drug release pattern. Thereinto, the granules, containing lactose as matrix and 9% (w/w) glyceryl behanate as coating, were regarded as the ones with the best release profile (26).…”
Section: Conventional Hot-melt Coating Techniquementioning
confidence: 99%
“…Commonly, reported binders such as polyethylene glycol, HPC, HPMC, PEO and HPMC in combination with lipid binders is used in melt granulation [5][6][7]. It has been reported in the literature that polymeric binders are not preferable when granulation process is developed for modified or controlled release applications due to solubility in ethanol and susceptibility to dose dumping in hydroalcoholic media [5][6][7]. To overcome the problem of polymeric meltable binders solid lipids are one ofmost viableoptions.…”
Section: Introductionmentioning
confidence: 99%